Interaction of Hydration Status and Physical Activity Level on Early Renal Damage in Children: A Longitudinal Study - Li, Menglong; Shu, Wen; Amaerjiang, Nubiya; Xiao, Huidi; Zunong, Jiawulan; Vermund, Sten H.; Huang, Dayong; Hu, Yifei (Frontiers in Nutrition, 2022)
Background: Optimal water intake positively affects various aspects of human physiology, especially renal function. Physical activity (PA) may have an impact on hydration status and renal health, but the interaction of hydration status and PA level on renal function is not well-studied in children. Methods: We conducted four waves of urine assays in our child cohort (PROC) study from October 2018 to November 2019 in Beijing, China. We measured urinary specific gravity, β2-microglobulin (β2-MG), and microalbumin (MA) excretion to assess hydration status and renal damage in the context of PA level and other covariates among 1,914 primary school children. We determined the associations of renal damage with the interaction of hydration status and PA level using generalized linear mixed-effects models. Results: The prevalence of dehydration was 35.0%, 62.1%, 63.9% and 63.3% and the prevalence of insufficient PA was 86.2%, 44.9%, 90.4% and 90.2% from wave 1 to wave 4 among 1,914 primary school children. From wave 1 to wave 4, the prevalence of renal tubular damage had a significant increasing trend of 8.8%, 15.9%, 25.7%, 29.0% (Z=16.9, P<0.001) while the prevalence of glomerular damage revealed a declining trend of 5.6%, 5.5%, 4.4%, 4.1% (Z=-2.4, P=0.016). There were stable longitudinal associations of renal tubular and glomerular damage with hydration status (euhydration: OR=0.50 and 0.33, respectively) but not with PA level. In multivariate analysis, significant interactions of hydration status and PA level were noted with renal tubular damage (β=0.43, P=0.014) and glomerular damage (β=0.60, P=0.047). Children with euhydration and insufficient PA were less likely to have renal tubular damage (OR=0.46, 95%CI: 0.39, 0.53) or glomerular damage (OR=0.28, 95%CI: 0.20, 0.39); children with euhydration and sufficient PA also were less likely to have renal tubular damage (OR=0.57, 95%CI: 0.44, 0.75) or glomerular damage (OR=0.47, 95%CI: 0.30, 0.74), adjusting for age, sex, BMI z-score, standardized SBP, sleep duration, computer/cell phone screen time, and fruit and vegetable intake. Conclusion: Children with euhydration and either sufficient or insufficient PA were less likely to have early renal damage. Adequate daily water intake for children is important, especially afer PA.